Persepsi Remaja tentang Seks Pranikah di Sekolah Menengah Atas - Alpiani, Delta; Widianti, Efri; Kosim, Kosim (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2021)
Premarital sex have a negative impact on adolescents’s biopsychosocial. Adolescents with positive perception towards premarital sex will avoid that behavior, while adolescents with negative perception prefer to do it. The purpose of this study was to determine how adolescent's perception of premarital sex in Senior High School in Tarogong Kaler Sub-District, The District of Garut. This study used descriptive quantitative research method with cluster sampling technique and was conducted by online survey during August 2020. The questionnaire was developed from the HBM (Health Belief Model) theory, as many as 320 adolescent respondents from class X, XI, and XII from 7 senior high schools at Tarogong Kaler Sub-District. The result indicated that perception of adolescents toward premarital sex was that some adolescents (50.9%) had positive perceptions. While for other domains were (65%) for perceptions of susceptibility, (56.9%) for perception of the seriousness, the perception of benefits (66.3%), and the perception of obstacles (65.9%). The conclusion was that the majority of adolescents in supported to not having premarital sex in each of their domains. Even so, some adolescents still perceived that premarital sex isn’t that bad. To improve adolescent's perception of premarital sex, the nurses would give them deep counseling and health education.